Non tubercular bacillus etiologic from bacterial lung diseases - AM , Oubayyou; MA , Gagara Issoufou; Mounkaila S,; Traoré AS,; H , Moumouni (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Etiologic agent of lung diseases can be others bacteria different from tubercular bacillus. Their treatment is based on a probalistic antibiotherapy. This requires awareness of responsible germs identity in a given region, at all times. With the aim to better care of humane lung infections, a prospective study carried from 1st October 2013 to 30th September 2016. The biologic sample was broncho-alvéolaire fluid, pleural fluid and sputum. At this given period, 247 samples were collected and examined. Bacteriological conventional methods were performed to detect warms in clinical samples. Ninety-one (91) bacteria strains were identified. Their characteristics showed Gram-negative rods group was most represented with 53.86%. Stenotrophomonas maltophilia occupy the first rang 14.28% of isolated species in this group. The Gram-positive cocci group was isolated at 46.14%, among which Staphylococcus aureus species occupied 24.17%. Diversity of bacteria species in pulmonary infection was showed through the study. That allow to a better chance of success in diagnosis, and probabilistic treatment in the country.